Utilizing Educational Media in the Field of Education Fosters Active Learning Within the Classroom - Aisyah R.D.N Padang; Melyani Sari Sitepu (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2023)
This study examines the use of learning media in the world of education to create active learning in the classroom. This study uses a qualitative approach, which describes and describes the use of instructional media in the world of education. The data collection technique used in this research is library research, where library research is the activity of collecting research-related materials from scientific journals, literature, and authors. The data in this study are based on books and journals that are relevant to the author's research. The data analysis technique used in this study is qualitative data analysis where in this study the opinions expressed by experts regarding instructional media, these data are used as a basis for strengthening the author's arguments in analyzing the effect of using instructional media. The results of this study indicate that learning media is needed in the teaching and learning process, the role of learning media is very important in the world of education where learning media can support the teaching and learning process of students and teachers. The influence of the use of learning media on learning makes teaching and learning easier for students and teachers, which can increase student motivation because teaching materials are used in the form of media. Learning attracts students' attention. The meaning of teaching materials becomes clearer, so that students understand more and learn to master the objectives of teaching materials.